Peran Pendidikan Kewarganegaraan dalam Membentuk Karakter Nasional Generasi Z - Dedek Agustianingsih; Susiba Susiba; Nabila Az-zahra; Selvia Rahma Sari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Civic Education has a key function in building the character of the younger generation amidst the complex issues of globalisation. This research aims to explore the contribution of Citizenship Education in shaping the character of an adaptive and nationalist Generation Z. The method used is library research by analysing various accredited journals and scientific articles related to learning theory, morals, character, citizenship, and globalisation. The research process was conducted by reading, summarising, and developing the information obtained. The results show that the implementation of Civic Education that focuses on experience, ethical values and digital technology can build critical attitudes, nationalism and a sense of social responsibility among the younger generation. This research shows that an approach that suits the character of digital natives is essential to keep civic values relevant and contextualised in modern times.